THE RELEVANCE OF USING DINAR AND DIRHAM IN THE ERA OF SOCIETY 5.0 - Mahlel (Journal of Islamic Studies [Z-ISLAMICA], 2025)
This research utilizes a qualitative method with a literature study approach to explore the restoration of the use of gold dinars and silver dirhams as currency from an Islamic perspective. The advantages of dinar and dirham, such as rust resistance, luxury, global acceptance, flexibility, and scarcity, are outlined with reference to the works of Imam al-Ghazali and other reliable literature. Despite these advantages, the implementation of the dinar and dirham faced a number of problems, including a lack of political and legal support from Muslim governments, as well as resistance from Western countries that could destabilize their economic dominance. The history of inflation in the period of dinar and dirham use is detailed, highlighting causes such as hoarding and counterfeiting that hurt the value of gold and silver currencies. While there is a desire to restore the use of dinar and dirham, real challenges involve a lack of political support, legal incompatibilities and global resistance. The research analysis confirms that in an Era Society 5.0 that relies heavily on technology and digital finance, the concept of restoring dinars and dirhams is no longer relevant, as people prefer digital currencies and modern financial innovations for better security, efficiency, and accessibility.